Copper-catalyzed yne-allylic substitutions: concept and recent developments - Yang, Shuang; Fang, Xinqiang (Beilstein Journal of Organic Chemistry, 2024)
The catalytic (asymmetric) allylation and propargylation have been established as powerful strategies allowing access to enantioenriched α-chiral alkenes and alkynes. In this context, combining allylic and propargylic substitutions offers new opportunities to expand the scope of transition metal-catalyzed substitution reactions. Since its discovery in 2022, copper-catalyzed yne-allylic substitution has undergone rapid development and significant progress has been made using the key copper vinyl allenylidene intermediates. This review summarizes the developments and illustrates the influences of copper salt, ligand, and substitution pattern of the substrate on the regioselectivity and stereoselectivity.
Keywords: copper-catalysis; copper vinyl allenylidene intermediate; 1,3-enyne; 1,4-enyne; yne-allylic substitution